THE DIMENSIONS OF ELECTRONIC (E)-BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION: EVIDENCE FROM NIGERIA - Olusola Enitan OLOWOFELA; Benjamin Oludotun LISOYI; Kehinde Isaiq OLAIYA (Modern Management Review)
This study investigates the dimensions of electronic (e)-banking service quality on customer satisfaction. The data were collected among bank customers within Lagos State, Nigeria vis a vis a validated closed-ended questionnaire from a sample of three hundred and eighty-three (383) questionnaires were returned. Descriptive analysis and regression analysis were used to analyse the data collected and test the study hypothesis. The results of this study revealed that ease to use, reliability and security have a positive significant impact on customer satisfaction. This shows that customers will be satisfied and be willing to use e-banking platform if it is easy to use, reliable and there is privacy for the financial transactions. The findings of this study has significantly contributed to academics and practitioners in the area of behavioral finance and likewise understand the need of different segment of customers of financial institutions.